Predictors of viral suppression among youth living with HIV in the southern United States. Issue 7 (2nd July 2020) - Tarantino, Nicholas; Whiteley, Laura; Craker, Lacey; Brown, Larry K.
ABSTRACT: Youth living with HIV (YLH) in the United States (U.S.) face significant problems with achieving viral suppression, especially in the South. To examine this issue, YLH with a detectable viral load ( N = 61) were recruited from the southern U.S and assessed over 16 weeks for health and treatment factors. Participants were part of a smartphone-based intervention trial. Analyses focused on predictors of viral suppression controlling for intervention effects. Fifty-three percent achieved suppression. In univariate models, YLH who engaged in condomless sex four to 16 weeks into the study (odds ratio [ OR ] = 4.00; compared to those who did not) and self-reported ≥ 90% antiretroviral adherence in the first four weeks of the study ( OR = 25.00; compared to youth with <90%) had a higher likelihood of suppression. Shifts in adherence-related social support ( OR = 4.98) and appointments kept ( OR = 2.72) were also associated with suppression. YLH endorsing illicit drug use had a lower likelihood of suppression ( OR = 0.16; compared to those without use). Effects (except drug use) remained significant or approached significance in a multivariate model. Adherence promotion efforts should consider this population's adherence-related social support, drug use, and risk for sexually transmitted infections.